2021
DOI: 10.1186/s13059-021-02410-2
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of N6-methyladenine RNA modification in interactions between rice and plant viruses

Abstract: Background N6-methyladenosine (m6A) is the most common RNA modification in eukaryotes and has been implicated as a novel epigenetic marker that is involved in various biological processes. The pattern and functional dissection of m6A in the regulation of several major human viral diseases have already been reported. However, the patterns and functions of m6A distribution in plant disease bursting remain largely unknown. Results We analyse the high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 114 publications
0
52
0
Order By: Relevance
“…Since m 6 A methylation has been widely reported to be involved in regulating biological processes in plants [ 24 , 25 , 28 , 31 , 33 , 62 ], we performed gene ontology (GO) enrichment analyses of m 6 A-containing genes in control- and drought-treated M. prunifolia seedlings. As shown in Figure 2 a,b, the m 6 A-containing genes in M. prunifolia under control and drought were significantly enriched in a number of pathways: (1) RNA processing: RNA processing, RNA splicing, ncRNA (metabolic) processing, and tRNA (metabolic) processing; (2) others: RNA 3′-end processing, mRNA transport, histone modification, regulation of gene expression, chromosome (chromatin) organization, and DNA methylation or demethylation; (3) development: flower development, fruit development, and post-embryonic development; (4) stress: response to abiotic stimulus, response to osmotic stress, response to heat, response to temperature stimulus, response to salt stress, response to stimulus, response to abiotic stimulus, response to metal ion, immune response, protein folding, and fatty acid metabolic process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since m 6 A methylation has been widely reported to be involved in regulating biological processes in plants [ 24 , 25 , 28 , 31 , 33 , 62 ], we performed gene ontology (GO) enrichment analyses of m 6 A-containing genes in control- and drought-treated M. prunifolia seedlings. As shown in Figure 2 a,b, the m 6 A-containing genes in M. prunifolia under control and drought were significantly enriched in a number of pathways: (1) RNA processing: RNA processing, RNA splicing, ncRNA (metabolic) processing, and tRNA (metabolic) processing; (2) others: RNA 3′-end processing, mRNA transport, histone modification, regulation of gene expression, chromosome (chromatin) organization, and DNA methylation or demethylation; (3) development: flower development, fruit development, and post-embryonic development; (4) stress: response to abiotic stimulus, response to osmotic stress, response to heat, response to temperature stimulus, response to salt stress, response to stimulus, response to abiotic stimulus, response to metal ion, immune response, protein folding, and fatty acid metabolic process.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with wild-type Arabidopsis , the alkbh6 mutant plants exhibit low survival rates under abiotic stresses, including salt, drought, and heat stresses [ 30 ]. Increased levels of m 6 A methylation have been observed in rice plants’ response to viral infection [ 31 ]. In maize, m 6 A hypomethylation under drought stress has a favorable function in drought response [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, total RNA was extracted and fragmented into approximately 200 nucleotide-long fragments. These fragments were incubated and purified as previous reported [ 15 ]. m 6 A-seq was performed on the Illumina HiSeq platform at Shanghai OE Biotech Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…In tobacco, the global m 6 A level was reduced under Tobacco mosaic virus (TMV) infection, probably associated with decreased m 6 A methyltransferase and increased demethylase expression [ 14 ]. Furthermore, m 6 A levels in susceptible rice increased in response to Rice black-streaked dwarf virus (RBSDV) and Rice stripe virus (RSV) infection, as m 6 A methylation mainly depends on genes which are not actively expressed in virus-infected rice plants via m 6 A-seq analyses [ 15 ]. In wheat, the transcriptome-wide m 6 A profile of two varieties with different resistance to Wheat yellow mosaic virus (WYMV) revealed that many genes related to plant defense responses and plant-pathogen interaction significantly changed in both m 6 A and mRNA levels [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings implied that the multifaceted effects of m 6 A modification on mRNA expression may depend on the position of m 6 A peaks in gene structure. The specific feature of m 6 A distribution in tea leaves is closely related to gene expression, and it is conserved among several important crops, including rice [36], strawberry [13], and apple [37].…”
Section: Analysis Of Dmp-associated Genesmentioning
confidence: 99%